Observations on Fevers and Other Diseases Which Occur on Voyages to Africa and the West Indies - Robertson, Robert (Cambridge library collection. History of Medicine, 1792)
Robert Robertson (1742–1829) was a Scottish doctor and surgeon. After completing his medical apprenticeship, Robertson joined the Royal Navy as a surgeon's mate in 1760. In 1768 he was appointed surgeon to the sloop Diligence, and served as surgeon on various ships in the West Indies, North America and west Africa until 1783. He was appointed surgeon to the Royal Hospital, Greenwich in 1793. This volume, first published in 1792, contains Robertson's detailed observations of malarial and yellow fever, dysentery and other diseases which he encountered while serving as surgeon in the West Indies. Robertson describes in detail the symptoms and progression of these diseases, his treatments and the outcomes, as recorded in his monthly reviews of the ships' sick lists and many detailed case histories of his patients. This volume provides valuable information concerning the treatment of common diseases and conditions on board late eighteenth-century naval ships